PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE TERHADAP AKTIVITAS DAN PRESTASI BELAJAR MAHASISWA DALAM MEMAHAMI MATERI KONGRUENSI - Fitria Yunaini (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2017)
Base on student, number theory is one of difficult subject. This subject learns about congruence which one of material that must mastered by student because of this subject become alternatif to solve about congruence problem in elementary and high school. Learning methode that used by reseacher is Think Pair Share. This learning use couple methode that continue by discusion. Using this methode, student will be trained to give idea commonly and learn to tolerare people’s idea in learning. The aim of the reseach is describe learning methode using Think Pair Share to increase activity and ability student in congruence subject at STKIP PGRI Blitar. The result of research is shown that by using TPS, lecturer activity is increasing from 90% in first meeting become 92,5% in second meeting and increasing of student activity from 82,5% in first meeting become 90% in second meeting. Student learning outcomes are seen from last evaluation 91,67% that means learning is complete clasically.